2019
DOI: 10.32527/2019/101382
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Induced Allosteric Effects Governing SR Signaling

Abstract: Steroid receptors (SRs) are a class of ligand-regulated transcription factors that regulate gene expression in response to the binding of steroid hormones. Ligand binding drives conformational changes within the SR ligand binding domain that alters the receptors' affinity for coregulator proteins that in turn modulate chromatin state and either promote or block the recruitment of transcriptional machinery to a gene. Structural characterizations of SRs have provided insight into how these conformational rearran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 136 publications
(165 reference statements)
1
22
0
Order By: Relevance
“…Crystal structures of GR LBD in complex with different ligands and coregulator peptides have shown that the receptor can adopt different conformations (5)(6)(7)9). In particular, the position of helix 12 is of key importance for receptor activity across the nuclear hormone receptor family (13)(14)(15)(16)(17). Recent reports on one other nuclear hormone receptor, the peroxisome proliferator-activated receptor  (PPAR), have demonstrated that helix 12 and the coregulatorbinding surface adopt an ensemble of conformations, the relative populations of which respond to ligand binding (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Crystal structures of GR LBD in complex with different ligands and coregulator peptides have shown that the receptor can adopt different conformations (5)(6)(7)9). In particular, the position of helix 12 is of key importance for receptor activity across the nuclear hormone receptor family (13)(14)(15)(16)(17). Recent reports on one other nuclear hormone receptor, the peroxisome proliferator-activated receptor  (PPAR), have demonstrated that helix 12 and the coregulatorbinding surface adopt an ensemble of conformations, the relative populations of which respond to ligand binding (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…A poorly understood phenomenon in protein evolution is how dynamical features are altered as proteins evolve new function. SRs are allosterically regulated; ligand binding induces a conformational switch that triggers a host of downstream transcriptional events (Okafor et al, 2019). This allosteric mechanism is conserved in two early ancestors of the SR family (Thornton, 2001(Thornton, , 2004Thornton et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the absence of ligand, the PPARγ LBD is conformationally dynamic, samples multiple conformation, and binding of an agonist stabilizes the LBD in an active conformation to a degree correlated with the activity of the ligand (18,(23)(24)(25). The association between ligand-bound NR LBD conformation and graded function is evidence for conformational selection in the mechanism of NR ligand activity (13,15,(19)(20)(21)(22)53). However, these studies only address the functional mechanism of the ligand-bound state; they do not address the mechanism of ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular simulations of ligand binding to steroid receptors including androgen receptor (AR), estrogen receptor alpha (ERα), glucocorticoid receptor (GR), mineralocorticoid receptor (MR), and progesterone receptor (PR) also suggest an induced fit mechanism (9,10), although the site of ligand entry into the orthosteric pocket is different than FXR (7) and PPARγ (8). Indeed, ligand binding to nuclear receptors is often described to induce an active conformation (4,(11)(12)(13)(14)(15)(16). However, there is evidence from NMR studies on PPARγ that in the absence of ligand the apo-LBD exchanges between transcriptionally active and transcriptionally inactive/repressive conformations (17) suggesting a role for conformational selection in the ligand binding mechanism of NR agonists, which are thought to stabilize an active conformation from a dynamic ensemble of active and inactive/repressive conformations (15,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%